Workshop Menyulam Untuk Peningkatan Keterampilan Remaja Putri Desa Kedungotok Kecamatan Tembelang Jombang - Ino Angga Putra; Faisol Hidayatulloh; Nabila Anisya; Mirza Zamrotul Ilma Sari; Alvin Nurul Khusna (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2022)
The objectives of this community service activity are a) a) to increase the insight/knowledge of the youth about embroidery techniques and b) to improve the skills of the youth in making embroidery products. The implementation of this community service activity uses the workshop method. The workshop method is carried out with 2 (two) aspects, namely a) delivery of material on embroidery techniques and b) training in making embroidery products. This community service activity was carried out covering 3 (three) activities, including a) coordination with partners, namely youth organizations in Kedungotok Village, Tembelang Jombang District, b) preparation of workshop tools and materials, and c) implementation of workshop activities. This activity was attended by 20 young women in Kedungotok Village, Tembelang District, which was held at the Kedungotok Village Hall, Tembelang District, Jombang. The workshop activity was carried out on October 25-31 2021. The data for this community service activity was carried out through an assessment of participants' understanding of embroidery techniques and an assessment of participants' skills in making embroidery products. The results of the implementation of community service activities were obtained: a) the understanding of the young women increased by 24.56% where the percentage of understanding of the participants before the activity was 60.09% and the percentage of understanding of the participants after participating in the activity was 84.65%, b) the skills of the youth of Dusun Kedungboto Kedungotok Village, Tembelang Jombang Sub-district, belongs to the “High” category where 80% of participants in the high category and 20% of participants in the moderate category, and c) the average skill score of the youth of Kedungboto Hamlet, Kedungotok Village, Tembelang Jombang District is at a high average score. of 3.4. These products made by young women become a superior product of Kedungotok Village in entrepreneurship and awaken local MSME business actors to be able to compete with other business actors.